Biochemical characterization of an organic solvent‐tolerant glycosyltransferase from Bacillus licheniformis PI15 with potential application for raspberry ketone glycoside production. (3rd December 2019) - Li, Bingfeng; Fan, Bo; Fan, Jingping; Chang, Siyuan; Pan, Xin; Wang, Yinan; Wu, Yaming; Song, Junsong; He, Xuejun
Abstract: Raspberry ketone is a primary aroma component of the red raspberry. The glycosylation of this compound is a potential approach used to improve its pharmaceutical properties. In this work, raspberry ketone glycosides are produced in bacteria for the first time. Bacillus licheniformis PI15, an organic solvent‐tolerant glycosyltransferase‐producing strain, was isolated from chemically polluted soil. The cloning and heterologous expression of a glycosyltransferase, which was designated PI‐GT1, in Escherichia coli BL21 resulted in the expression of an active and soluble protein that accounted for 15% of the total cell protein content. Purified PI‐GT1 was highly active and stable over a broad pH range (6.0–10.0) and showed excellent pH stability. PI‐GT1 maintained almost 60% of its maximal activity after 3 H of incubation at 20–40 °C and demonstrated optimal activity at 30 °C. Additionally, PI‐GT1 displayed high stability and activity in the presence of hydrophilic solvents with log P ≤ −0.2 and retained more than 80% of its activity after 3 H of treatment. Supplementation with 10% DMSO markedly improved the glycosylation of raspberry ketone, resulting in a value 26 times higher than that in aqueous solution. The organic solvent‐tolerant PI‐GT1 may have potential uses in industrial chemical and pharmaceutical synthesis applications. Abstract : Scheme of raspberry ketone glycosides are produced by Bacillus licheniformis PI15